The case of the deadly desperados - Lawrence, Caroline (Western mysteries ;, 2011)
In 1862 Nevada Territory, after finding his foster parents murdered and scalped, twelve-year-old Pinky Pinkerton, son of a railroad detective and a Sioux Indian, inherits a valuable deed and must hide from dangerous Whittlin Walt and his gang of desperados.